2016
DOI: 10.3390/ijerph13111081
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene and Pyrene Modify the Composition and Structure of the Cultivable Endophytic Bacterial Community in Ryegrass (Lolium multiflorum Lam)

Abstract: This study provides new insights into the dynamics of bacterial community structure during phytoremediation. The communities of cultivable autochthonous endophytic bacteria in ryegrass exposed to polycyclic aromatic hydrocarbons (PAHs) were investigated with regard to their potential to biodegrade PAHs. Bacterial counts and 16S rRNA gene sequence were used in the microbiological evaluation. A total of 33 endophytic bacterial strains were isolated from ryegrass plants, which represented 15 different genera and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Interestingly, co-isolation of strains did not appear to be an important factor for their ability to engage in a social behavior, and even our canonical two species were not co-isolated, one having been isolated in Dutch dune soil, and the other from sandy-loam soil in a farm in MA, U.S.A (33,34). The vast majority of the species we tested were isolated from soil, but Pseudomonas and Pedobacter can be isolated from a variety of different environments (35)(36)(37)(38)(39)(40). Ultimately, close relationship to our initial two study strains is a better predictor of interaction than the environment from which the strains were isolated.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, co-isolation of strains did not appear to be an important factor for their ability to engage in a social behavior, and even our canonical two species were not co-isolated, one having been isolated in Dutch dune soil, and the other from sandy-loam soil in a farm in MA, U.S.A (33,34). The vast majority of the species we tested were isolated from soil, but Pseudomonas and Pedobacter can be isolated from a variety of different environments (35)(36)(37)(38)(39)(40). Ultimately, close relationship to our initial two study strains is a better predictor of interaction than the environment from which the strains were isolated.…”
Section: Discussionmentioning
confidence: 75%
“…Gammaproteobacteria and Alphaproteobacteria endophytes were more abundant in roots, while Betaproteobacteria were predominant in stems [122]. In turn, the abundance analysis indicated that the exposure of ryegrass to increasing concentrations of phenanthrene and pyrene positively correlated with the numbers of endophytic bacteria and negatively correlated with the richness of these communities in roots, while no such relationship was con-firmed for shoots [25]. Similar data related to endophyte biodiversity in wheat depending on the phenanthrene contamination level were reported by Liu et al [26].…”
Section: Methods Of Selecting Endophytic Strains With Biodegradation Potentialmentioning
confidence: 91%
“…This may suggest their potential for biodegradation of the hydrocarbons tested. Moreover, it was shown that the higher concentrations of individual or combined PAHs were accompanied by lower biodiversity of endophytes [25]. In turn, it was found in another study that inoculation of phenanthrene-contaminated wheat with PAH-degrading endophytic Massilia sp.…”
Section: Removal Of Hydrocarbonsmentioning
confidence: 96%
See 1 more Smart Citation
“…2 ), strain VsBac-Y9 was affiliated with the cluster composed of the above-described clone sequences and Rhizobium sp, enrichment clone N312. A BLAST search of its almost-complete 16S rRNA gene sequence (1387 bp) with the NCBI database showed that isolate VsBac-Y9 was extremely close to the Rhizobium isolates P7 and YIC4260, which were cultured from the rhizospheres of gramineous Lolium multiflorum ( 37 ) and leguminous Sesbania cannabina ( 21 ), respectively.…”
mentioning
confidence: 99%